Mimetic Theory and Its Shadow : Girard, Milbank, and Ontological Violence - Cowdell, Scott (Book collections on Project MUSE., 2023)
"Cowdell shows how Girard's vision of human transformation through faith in Christ reveals a different world beyond ontological violence while preserving the divine participation that Milbank champions"--